Attenuation of Muscle Mass and Density Is Associated With Poor Outcomes Among Patients Undergoing Major Gynecologic Surgery: A Retrospective Cohort Study. (25th January 2021) - Che, Lu; Zhang, Yan; Yu, Jiawen; Xu, Li; Huang, Yuguang
Abstract : BACKGROUND: The aim of this study was to explore the associations of preoperative sarcopenia (muscle mass depletion) and myosteatosis (muscle quality attenuation) with the incidence of postinduction hypotension (PIH) and postoperative complications among patients undergoing major gynecologic surgery. METHODS: Based on a previous prospective surgical registry of gynecologic patients, we included patients with an available preoperative abdominal computed tomography (CT) scan performed within 3 months before surgery. The cross-sectional muscle mass and density at the third lumbar vertebra (L3) level were measured from the CT scan. The primary outcome was PIH, which was defined as a blood pressure reduction >30% from baseline. The secondary outcome was postoperative complications based on the Clavien-Dindo classification. Multivariable logistic regression analyses were performed to identify the associations between the muscle parameters and outcomes. RESULTS: Of the 167 gynecologic surgical patients included in this study, the mean (standard deviation [SD]) age was 53.0 (12.2) years. Sarcopenia was present in 86 (51.5%) patients. Fifty-six (33.5%) patients experienced PIH, and 89 (53.3%) patients experienced different degrees of postoperative complications. Multivariable analysis showed that myosteatosis was significantly associated with an increased risk of PIH (odds ratio [OR] = 2.95, 95% confidence interval [CI], 1.24-7.04; P = .015), and sarcopenia was associated with an increased risk of postoperative complications (OR = 2.30; 95% CI, 1.16-4.57; P = .018). CONCLUSIONS: Muscle assessments using preoperative CT scans may help identify high-risk patients and determine perioperative management strategies among gynecologic patients.